Japan's Policy towards Korea 1876-1910 - Kefah Juma’a Wajar (Zanco Journal of Human Sciences, 2025)
Japan had sought to interfere in Korea’s affairs and control it since the Meiji reign, it made great efforts before 1876 to break Korean isolation to gain a foothold in it. In 1876, Japan had forced Korea to sign the Ganghwa Agreement, under which, it gained a political and economic foothold, but it faced competition from China, which considered that Korea belongs to it, but this competition had led to a rebellion in Korea, where both countries sent their forces to protect their subjects. In 1894 when a rebellion occurred in Korea, as a result the Japanese forces had arrived and refused to withdraw, so a war had broken out between Japan and China, that war had ended with the defeat of China and the consolidation of Japanese influence in Korea. Similarly, Japan entered into a confrontation with Russia that led to the outbreak of war in 1904, which ended with Russia's defeat too, during that war, Japan imposed a protection agreement on Korea. In 1907, the Korean king was forced to abdicate in favor of his son, then the Cabinet was dissolved and a ministry loyal to Japan was formed, in the same year the Korean army was also dissolved and the Japanese presence in Korea had continued till 1910,when Japan annexed Korea to its territories